Exposure of androgen mimicking environmental chemicals enhances proliferation of prostate cancer (LNCaP) cells by inducing AR expression and epigenetic modifications. (1st March 2021) - Singh, Vipendra Kumar; Pal, Rajesh; Srivastava, Priyansh; Misra, Gauri; Shukla, Yogeshwer; Sharma, Pradeep Kumar
Abstract: Exposure to environmental endocrine disrupting chemicals (EDCs) is highly suspected in prostate carcinogenesis. Though, estrogenicity is the most studied behavior of EDCs, the androgenic potential of most of the EDCs remains elusive. This study investigates the androgen mimicking potential of some common EDCs and their effect in androgen-dependent prostate cancer (LNCaP) cells. Based on the In silico interaction study, all the 8 EDCs tested were found to interact with androgen receptor with different binding energies. Further, the luciferase reporter activity confirmed the androgen mimicking potential of 4 EDCs namely benzo[a]pyrene, dichlorvos, genistein and β-endosulfan. Whereas, aldrin, malathion, tebuconazole and DDT were reported as antiandrogenic in luciferase reporter activity assay. Next, the nanomolar concentration of androgen mimicking EDCs (benzo[a]pyrene, dichlorvos, genistein and β-endosulfan) significantly enhanced the expression of AR protein and subsequent nuclear translocation in LNCaP cells. Our In silico studies further demonstrated that androgenic EDCs also bind with epigenetic regulatory enzymes namely DNMT1 and HDAC1. Moreover, exposure to these EDCs enhanced the protein expression of DNMT1 and HDAC1 in LNCaP cells. These observations suggest that EDCs may regulate proliferation in androgen sensitive LNCaP cells by acting as androgen mimicking ligands for AR signaling as well as by regulating epigenetic machinery. Both androgenic potential and epigenetic modulatory effects of EDCs may underlie the development and growth of prostate cancer. Graphical abstract: Image 1 Highlights: Endocrine disrupting chemicals (EDCs) may act as an agonist to androgen receptor. Androgen mimicking EDCs enhance AR protein expression in androgen sensitive LNCaP cells. Androgen mimicking EDCs augment proliferation in LNCaP cells. EDCs modulate expression of epigenetic markers such as HDAC1 and DNMT1. EDCs may regulate prostate carcinogenesis via AR signaling and epigenetic modulations. Abstract : Our study highlights the androgen mimicking potential of estrogenic EDCs and their implication in proliferation of androgen-dependent prostate cancer.